Communalism and consociational democracy: a response to Abbas Assi. Issue 4 (1st October 2016) - Scheffler, Thomas
Abstract : A reply to: Assi, A. 2016. "Lebanon's consociational model, Christian parties and the struggle for political power in post-2005 period". Global Discourse 6 (4).http://dx.doi.org/10.1080/23269995.2016.1259230 .